Sistem Pendukung Keputusan Metode AHP untuk Penentuan Dosen dengan Kinerja Terbaik pada Fakultas Komputer di Universitas Universal - Cindy; Mie, Yoe; Venerik; Wibowo, Candra (Fakultas Komputer - Universitas Universal, 2024)
This research focuses on the implementation of a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method to determine the best-performing lecturer at the Faculty of Computer, Universitas Universal. The study aims to provide an objective and measurable evaluation of lecturer performance by considering criteria such as education, research, community service, and supporting activities. The results of the AHP calculation show that Lecturer 4 ranked first with the highest total score of 93.29, followed by Lecturer 8 with a score of 90.39, and Lecturer 13 with a score of 89.78. The AHP method offers a transparent and efficient approach to decision-making, which can motivate lecturers to improve their academic performance and contribute to creating a productive work culture at the faculty. This study concludes that the application of AHP in determining the best lecturer is an effective solution to ensure fair, transparent, and objective decisions, ultimately enhancing the overall academic quality.